Long-term durability of silicone breast implants - Vladimir V. Shadrin; Sergei A. Plaksin; Violetta A. Platunova (Exploration of BioMat-X)
Aim: The purpose of this study is to investigate the deformability and strength of silicone breast implant shells from different manufactures as a function of implantation time. Methods: The strength properties of about 200 shells of Eurosilicone, Mentor, Motiva, Allergan, Arion, PIP silicone breast implants removed for various reasons during repeated surgeries with a period of stay in the body from 6 months to 29 years were measured and compared with the corresponding properties of four shells of unused Eurosilicone and Motiva implants. Deformation was measured using a videoXtens extensometer. Results: The mechanical properties of the Allergan implant shell are almost completely consistent with the properties of the Eurosilicone shell after 9 years of use. The Mentor implants showed greater strength and stiffness. The Motiva implant shells initially had higher ultimate properties—rupture stress and rupture strain—in comparison with the Eurosilicone implant shells. Conclusions: The strength and deformation properties of all examined breast implant shells decrease in the course of time. After 13 years of use, the strength of breast implants is halved and their rupture strain is reduced by one third. The main mechanism responsible for loss of strength is the accumulation of microdamages during long-term use of breast implants. The thickness of the nano-textured shells of Motiva implants is twice less of the Eurosilicone implant shell thickness. This was possible due to a significant increase in the mechanical properties of Motiva shells.